2021
DOI: 10.1177/10499091211038303
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Unit at Home: Impact on Quality of Life in Cancer Patients at the End of Life in a Rural Environment

Abstract: Introduction: Advanced cancer is accompanied by a substantial burden of symptoms, and palliative care (PC) plays an essential role, especially at the end of life (EOL). In fact, a comprehensive PC through Home Palliative Care Units (HPCU) has been associated with reducing potentially aggressive care at the EOL. We aim to study the impact of HPCU on the quality of assistance of cancer patients at Alcoy Health Department. Methods: A retrospective study was conducted including patients diagnosed with terminal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The data from this ILR reinforce that RVH improve the quality of life of cancer patients, increase the length of stay at home and reduce the risk of RVH. 7,9,13,15,28,32 Despite the benefits offered by HPC, the percentage of cancer patients who resort to RVH is still high, either due to physical signs and symptoms inherent to the advanced stage of the disease; 6,7,9,15,19,[26][27][29][30][31][32][33][34][35] factors inherent to certain types of cancer; 6,9,13,26 social/family factors; 6,[32][33] cultural factors or characteristics of the healthcare network. 27,30,35 The increased risk of hospitalization in patients with hematologic tumors was demonstrated in two articles 9,13 of this review coinciding with previous study data 36 in which patients with non-solid tumors were more likely to die in hospital, which was attributed to the existence of multiple treatment options, even in advanced stages of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from this ILR reinforce that RVH improve the quality of life of cancer patients, increase the length of stay at home and reduce the risk of RVH. 7,9,13,15,28,32 Despite the benefits offered by HPC, the percentage of cancer patients who resort to RVH is still high, either due to physical signs and symptoms inherent to the advanced stage of the disease; 6,7,9,15,19,[26][27][29][30][31][32][33][34][35] factors inherent to certain types of cancer; 6,9,13,26 social/family factors; 6,[32][33] cultural factors or characteristics of the healthcare network. 27,30,35 The increased risk of hospitalization in patients with hematologic tumors was demonstrated in two articles 9,13 of this review coinciding with previous study data 36 in which patients with non-solid tumors were more likely to die in hospital, which was attributed to the existence of multiple treatment options, even in advanced stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5] The place where the patient wishes to receive care, including at the end of life, is usually at home, which requires preparation and structure to make this feasible. 4,[6][7] There are Home Care (HC) services specialized in PC oncology, whose benefits include favoring the relief of physical, psychological, social or spiritual signs and symptoms, reducing the demand for emergency care, avoiding unnecessary hospitalizations, reducing the death rate in the hospital environment and allowing patients to stay longer at home with their families, also reducing hospital costs. [8][9][10][11][12][13][14] However, cancer patients in Home Palliative Care (HPC) may require care in the emergency room in situations of complications and/or decline in general condition, caused by the natural evolution of the disease, effects of anticancer therapy or by lack of symptom control.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the substantial burden of symptoms and palliative care in advanced cancer, especially at the end of life, Moncho et al 7 described the role of Home Palliative Care Units (HPCU) in emergency department consultations in Spain. The authors found that lack of HPCU care was associated with a higher risk of emergency department consultation (OR = 1.29, 95% CI: 1.02–1.67), of hospital admissions (OR = 4.72, 95% CI: 2.45–9.09), and a higher probability of continuing active treatment (OR = 2.59, 95% CI: 1.44–4.67) and of dying in hospital (OR = 6.52, 95% CI: 3.78–11.27).…”
Section: Palliative Care Models In Resource‐limited Settingsmentioning
confidence: 99%
“…This could be also modified based on language and cultural characteristics to make people from a rural setting/resource-limited setting understand terms and concerns of palliative care therapy in cancer patients, since the complex terminology can be confusing to patients and their local caregivers. 5 These mentioned models [2][3][4] and examples [2][3][4][5] of palliative care between inaccessible case zones in low-cost and resource-limited settings draw our attention to the palliative care provided to individuals suffering from oncological problems (Figure 1). We thank the authors on their studies and possible models for the elaboration and implementation of new public health policies in this field.…”
Section: Respected Editormentioning
confidence: 99%